Semiotics and Cartomancy: Tartu-Moscow Semiotic School Legacy - Mattia Thibault (KOME: An International Journal of Pure Communication Inquiry, 2015)
This paper aims to reconstruct the fortune of the semiotic analysis of cartomancy, considered as a proper semiotic system, focusing in particular on the point of view of Tartu-Moscow School of Semiotics (TMS). TMS, founded by the renowned semiotician Yuri Lotman, offers one of the most interesting semiotic approaches to culture and communication yet is still partially ignored in the West with the exception, of course, of its founder. Many TMS scholars approached cartomancy not only as an interesting cultural phenomenon but as a case study allowing them to test analytic tools that fit for many different forms of communication. Cartomancy is, at the same time, a quite simple semiotic system and a very sophisticated cultural phenomenon; this makes it a very useful object of study, allowing us to manipulate an entire (and rich) language while looking for the basic workings of all kinds of communication. The article will show how TMS analysis of cartomancy has already been quite productive and has had a few entails as well as how these analyses could help us to reach a better understanding of play, which is one of the biggest challenges that communication studies are facing today.